Sauropod haemal arches: morphotypes, new classification and phylogenetic aspects - Otero, Alejandro (2011)
Sauropod haemal arches are caudal bony structures that have been traditionally incorporated into two different types observed in different anatomical views: Y-shaped (anterior view) and forked (lateral view). This research proposes a classification combining information observed in anterior and lateral views. Four types of ?Y-shaped? and six types of ?V-shaped? chevrons were recognised. Complete chevron series in some eusauropods allows the comparison of topological equivalent structures along the tail and also among taxa. A basal titanosaur from Argentina exhibits mid-caudal chevron morphology in which more than one cranial and caudal process is present, arising from the distal blades as well as from the proximal rami, a condition not seen before in a sauropod dinosaur. The morphological variability seen in sauropod chevrons along the tail is in close relationship with the development and distribution of muscle. caudofemoralis longus, as seen in extant crocodiles and as previously proposed for non-avian theropods and for caudal centra and transverse processes of sauropod dinosaurs. Two new characters related to middle chevrons are proposed here, in which the transitional morphology is described.